Impact of the 13-Valent Pneumococcal Conjugate Vaccine on Pneumococcal Carriage Among American Indians. Issue 8 (August 2016) - Grant, Lindsay R.; Hammitt, Laura L.; O'Brien, Sarah E.; Jacobs, Michael R.; Donaldson, Connie; Weatherholtz, Robert C.; Reid, Raymond; Santosham, Mathuram; O'Brien, Katherine L.
Abstract : Background: Community-wide impact of pneumococcal conjugate vaccines (PCV) is conferred by reductions in vaccine-type nasopharyngeal carriage. We evaluated the impact of PCV13 on carriage of PCV13-specific types (1, 3, 5, 6A, 7F and 19A) and 6C among American Indians. Methods: A nasopharyngeal specimen was collected from community members of all ages between January 2010 and April 2012 (3 months before and 24 months after PCV13 introduction). Pneumococci were isolated by culture and serotyped using antisera. Monthly carriage prevalence and PCV13 coverage were calculated to identify the timing of vaccine impact relative to PCV13 introduction. Prevalence ratios (PRs) were used to compare PCV13-specific carriage before and in years 1 and 2 of PCV13 use. Coverage was calculated according to age and number of doses received. Results: 6645 participants (2859 <5 years and 3786 ≥5 years of age) provided 6628 specimens. A decline in PCV13-specific and type 6C carriage among children <5 years of age was observed 9 and 15 months after PCV13 introduction, respectively. Among underimmunized children, a decline in PCV13-specific carriage was observed 11 months after PCV13 introduction, when coverage in the community reached 58%. In year 2 of PCV13 use, PCV13-specific and 6C carriage were reduced by 60% and 70%, respectively (PCV13 specific: PR = 0.4, P < 0.001; 6C: PR = 0.3, P < 0.001) among children <5 years of age. The reduction in PCV13-specific carriage among those 5 to <8 years and 18+ years of age in year 2 of PCV13 use was not statistically significant. Conclusions: PCV13 reduced PCV13-specific and 6C carriage among children <5 years of age. Low pre-PCV13 carriage prevalence of PCV13-specific types limited confirming this reduction for adults. Abstract : Supplemental Digital Content is available in the text.